Introducing the Sounds of Data to the Study of Politics: A Choir of Global Legitimacy Crises. Issue 3 (2nd July 2020) - Agné, Hans; Sommerer, Thomas; Angeler, David G.
ABSTRACT: This article introduces an innovative method to describe data with sounds in political science. The method, known in ecology, physics, and musicology as "sonification, " operates by linking sound signals to quantifiable observations. We us it to compose a choir of legitimacy crises in global governance from 1994 to 2014, and to negotiate a familiar divide in research on how legitimacy should be measured. Scholars predominantly prefer one of two approaches to measure legitimacy quantitatively, either looking at political trust or public contestation of political institutions. We illustrate the usefulness of sonification to subsume both positions in this divide. More generally, we argue that sonification can enhance public communication of scientific results and extract meanings from observations that go unnoticed in visual and verbal representations, in particular with relevance to describing time series data on anything from the spread of pandemics to violent conflicts and economic inequalities.